Ageing population risks - Pavel V. Shevchenko (MDPI, 2018)
An ageing population is a major challenge for every country in the world arising from the declining fertility rate and increasing life expectancy. A longevity risk (the adverse outcome of people living longer than expected) exacerbated by declining equity returns coupled with the record low interest rate environments has significant implications for societies and manifests as a systematic risk for providers of retirement income products. The aim of this special issue is to highlight advances in quantitative modelling of risks related to ageing population problems. It is aimed at practitioners and regulators in insurance, banking and pension industries; academic researchers; and advanced graduate students in the area.
Keywords: 330